The Effect of Leverage, Company Size, and Profitability on Tax Aggressiveness with Executive Character as a Moderation Variable - Alboin Sihombing; JMV Mulyadi (Journal of Social Research, 2023)
This study aims to test and analyze the effect of leverage variables, company size, and profitability on tax aggressiveness with executive character as a moderation variable. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The population in this study is invoice companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The number of samples selected by the purposive sampling method was 260 samples from 52 companies during five years of observation. The data analysis method used is Moderated Regression Analysis (MRA). The results showed that leverage and profitability had an effect on tax aggressiveness, while company size had no effect on tax aggressiveness. Executive character can strengthen moderation between the effect of leverage on tax aggressiveness , executive character can weaken moderation between the effect of profitability on tax aggressiveness.